2015
DOI: 10.1186/s12912-015-0083-9
|View full text |Cite
|
Sign up to set email alerts
|

Developing a student-led health and wellbeing clinic in an underserved community: collaborative learning, health outcomes and cost savings

Abstract: BackgroundThe University of New England (UNE), Australia decided to develop innovative placement opportunities for its increasing numbers of nursing students. Extensive community and stakeholder consultation determined that a community centre in rural New South Wales was the welcomed site of the student-led clinic because it fit the goals of the project—to increase access to health care services in an underserved area while providing service learning for students.MethodsSupported by a grant from Health Workfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…Research has demonstrated that student-led clinics are feasible for student learning (Ellett, Campbell, and Gonsalves, 2010;Simpson and Long, 2007) and provide a rich source of experiential practice in the context of direct patient care (Jokelainen et al, 2011). Student-led clinics also provide opportunities for health professional students to take responsibility for the logistics, operational management, and treatment of patients under the guidance and supervision of registered and licensed health professionals, thus facilitating professional socialization (Ernstzen, Blitzer, and Grimmer-Somers, 2009;Stuhlmiller and Tolchard, 2015). Research relating to student-led clinics has demonstrated increased student placement capacity (Frakes et al, 2011;Kent, 2012), as well as increased clinical experiences within an interprofessional environment (Moskowitz, Glasco, Johnson, and Wang, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that student-led clinics are feasible for student learning (Ellett, Campbell, and Gonsalves, 2010;Simpson and Long, 2007) and provide a rich source of experiential practice in the context of direct patient care (Jokelainen et al, 2011). Student-led clinics also provide opportunities for health professional students to take responsibility for the logistics, operational management, and treatment of patients under the guidance and supervision of registered and licensed health professionals, thus facilitating professional socialization (Ernstzen, Blitzer, and Grimmer-Somers, 2009;Stuhlmiller and Tolchard, 2015). Research relating to student-led clinics has demonstrated increased student placement capacity (Frakes et al, 2011;Kent, 2012), as well as increased clinical experiences within an interprofessional environment (Moskowitz, Glasco, Johnson, and Wang, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they are required to foster learning opportunities for students as well as provide them with feedback. Furthermore, the environment is often less private than other healthcare settings, with patients also frequently needing to set aside more time for a consultation than they would in a non-student-led clinic (Stuhlmiller and Tolchard, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Free and charitable healthcare services over time have filled the gap for patients needing medical assistance without the financial means, especially in the United States [44]. Likewise a SRC at the University of New England, Australia, was estimated to save the healthcare system around $437,000.00 in 2013/2014 [45]. This was determined through savings from averting visits to the emergency department.…”
Section: Implications For Health and Researchmentioning
confidence: 99%
“…In 2012, the first Australian SRC began providing medical, nursing, social work and physiotherapy services in Melbourne, and similar clinics have also sprouted in New South Wales and Queensland . In the same vein, medical students from Flinders University in Adelaide piloted the Flinders Student Run Clinic (FSRC), with the support of faculty and of the Vinnie's Men's Crisis Centre, which provides crisis accommodation, meals, showers and case management for up to 47 homeless and vulnerable men aged over 18 years.…”
mentioning
confidence: 99%